Impacts of Firm Internationalization, Green Procurement and Organizational Performance of University College Hospital, Ibadan, Nigeria - Oyedokun, Godwin Emmanuel; Garba, Mariam Abiola (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The procurement system invariably suffers various forms of malpractices and unethical conduct which includes a high incidence of vested interest, contract inflation, delay in suppliers’ payment, and increased procurement cycle. The review explored impacts of firm internationalization, green procurement and organizational performance of University College Hospital (UCH), Ibadan. Theory considered for this study is the agency theory. Descriptive and survey design was embraced for the review. The populace in the review contained 158. A stratified sampling technique was used and the strata’s are procurement, stores, payment units (Account), and the different end user’s department. An organized poll was directed. The instrument was approved, and the information assembled was broken down utilizing mean standard deviation, and correlation analysis. Out of the 158 polls directed, 136 were recovered (86% reaction rate). The review discovered that green procurement (mean worth 4.3145), negotiation management (mean worth 4.2581), competitive bidding (mean worth 4.2581) and its correlation co-efficient: (green procurement 0.214, negotiation management 0.737, competitive bidding 0.230) was found to have a positive and significant effect on organizational performance of UCH, Ibadan. The study subsequently inferred that green procurement did not lead to client’s satisfaction. However, green procurement leads to an increase in service quality, product quality, source reduction and waste management. Based on the findings, it is therefore recommended that more financial resources should be made available for the acquisition of substitute products and public awareness on the need to conserve the environment through green procurement.